2013
DOI: 10.1007/978-3-642-40991-2_27
|View full text |Cite
|
Sign up to set email alerts
|

Multi-label Classification with Output Kernels

Abstract: Abstract. Although multi-label classification has become an increasingly important problem in machine learning, current approaches remain restricted to learning in the original label space (or in a simple linear projection of the original label space). Instead, we propose to use kernels on output label vectors to significantly expand the forms of label dependence that can be captured. The main challenge is to reformulate standard multi-label losses to handle kernels between output vectors. We first demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…In contrast, in joint SVM, the dependency between different tags are encoded in output kernels. In this sense, our work is also similar to LM-K [18] and M3L [4]. Interestingly, when the output kernel is linear, it is equivalent to the explicit relationship learning in MLRL.…”
Section: Related Workmentioning
confidence: 66%
See 3 more Smart Citations
“…In contrast, in joint SVM, the dependency between different tags are encoded in output kernels. In this sense, our work is also similar to LM-K [18] and M3L [4]. Interestingly, when the output kernel is linear, it is equivalent to the explicit relationship learning in MLRL.…”
Section: Related Workmentioning
confidence: 66%
“…To transform the pairwise and triplet-wise dependencies between tags into the inner product of two outputs containing those tags, 2-degree and 3-degree polynomial kernels are tried in [18] and it was reported that 2-degree is better than 3-degree. In [4,16,20], linear feature maps were exploited also for pairwise dependencies.…”
Section: Implicit and Explicit Linear Output Kernels On Tag-setsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the complexity of patterns captured by biological images, these shallow models of feature extraction may not be sufficient. Therefore, it is desirable to develop a multilayer feature extractor [7], [32], [33], alleviating the tedious process of manual feature engineering and enhancing the representation power.…”
Section: Introductionmentioning
confidence: 99%